2009
DOI: 10.1111/j.1365-2133.2008.09020.x
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis and risk of incident myocardial infarction, stroke or transient ischaemic attack: an inception cohort study with a nested case-control analysis

Abstract: The risk of developing a cardiovascular outcome was not materially elevated for patients with early psoriasis overall. In subanalyses, however, there was a suggestion of an increased (but low absolute) MI risk for patients with psoriasis aged < 60 years, mainly with severe disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
156
0
7

Year Published

2011
2011
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(180 citation statements)
references
References 49 publications
17
156
0
7
Order By: Relevance
“…73 A recent inception cohort study with nested case-control analysis identified an increased risk of incident MI in patients less than 60 years old with severe disease, but failed to detect increases in strokes or TIA. 74 Similarly, in the Netherlands, patients with psoriasis did not have increased hospitalizations from ischemic heart disease. 75 To the contrary, in China, there was a higher odds ratio for the development of MI for mild and severe psoriasis, even after adjusting for age, sex, DM, HTN, hyperlipidemia, smoking and systemic therapies.…”
Section: -mentioning
confidence: 95%
“…73 A recent inception cohort study with nested case-control analysis identified an increased risk of incident MI in patients less than 60 years old with severe disease, but failed to detect increases in strokes or TIA. 74 Similarly, in the Netherlands, patients with psoriasis did not have increased hospitalizations from ischemic heart disease. 75 To the contrary, in China, there was a higher odds ratio for the development of MI for mild and severe psoriasis, even after adjusting for age, sex, DM, HTN, hyperlipidemia, smoking and systemic therapies.…”
Section: -mentioning
confidence: 95%
“…A modestly increased prevalence of MI was observed in both psoriasis and PsA patients, which varied with age 11,12 and psoriasis severity. 11,13,14 It remained significantly elevated after controlling for major cardiovascular risk factors.…”
Section: Cardiovascular Morbidity and Mortalitymentioning
confidence: 94%
“…A descriptive cohort study has newly shown that patients with psoriasis had higher risks of incident myocardial infarction, angina, atherosclerosis, peripheral vascular disease, and stroke (5). Additionally, the prevalence of MI is higher in mild and severe psoriasis than in patients without psoriasis (29,30). There have been studies which have connected psoriasis to metabolic syndrome (31)(32)(33)(34).…”
Section: Relationship Between Psoriasis and Cardiovascular Diseasesmentioning
confidence: 99%